Study of Performance of Suspended Flat Plate air Heater - Yakhour, Y (Al-Mukhtar Journal of Sciences, 2022)
In this communication, a heat transfer model to predict the transient behaviour of a suspended flat plate solar collector with constant flow of fluid (air) above the absorber has been presented. A reflection sheet with an air gap between the absorber plate and bottom insulation to reduce heat loss, has been used. The effect, on performance of the heater, of the parameters viz, spacing between cover and plate, heat capacity of air and absorber plat, flow rate of fluid and collector length have been studied. The effect of changing the averaging inlet temperature varying collector length has also been studied.